(untitled) (Universitas Scientiarum, 2003)
The nula number was introduced by L. Lareo and O. Acevedo in order to represent the information that sequences of nucleotides carry on. We want to identify some algebraic properties on the nula set, providing it with an operation and locking for the properties that this operation holds.